The Effect Of Green Banking Practices On Sustainability Performance With Green Finance As A Mediation Variable - Widowati, Kunthi; Chariri, Anis (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to examine the influence of Green Banking Practices on Sustainability Performance with Green Finance as a mediating variable. The research focuses on four key objectives: analyzing the effect of Green Banking Practices on Green Finance, assessing the impact of Green Finance on Sustainability Performance, examining the direct influence of Green Banking Practices on Sustainability Performance, and evaluating the mediating role of Green Finance in this relationship. A quantitative approach with an exploratory research design was applied to obtain empirical insights into the implementation of green banking and its implications for sustainability outcomes. The population consists of 61 banks in Central Java, and the sample was selected using purposive sampling, resulting in 120 respondents from banks that have adopted green banking practices and implemented green finance programs. Data were collected through questionnaires and literature studies, then analyzed using Structural Equation Modeling with Partial Least Square (SEM-PLS) through SmartPLS 4.0. The findings reveal that Green Banking Practices positively influence Green Finance, Green Finance significantly enhances Sustainability Performance, and Green Banking Practices directly improve Sustainability Performance. Furthermore, Green Finance mediates the effect of Green Banking Practices on Sustainability Performance. These results emphasize the strategic importance of green banking policies and green financing mechanisms in strengthening the sustainability performance of banking institutions.